Impact of microcredit program on poverty reduction among rural households in Saki East Local Government area of Oyo State, Nigeria - Yaqoob, Abdul Majeed; Yusuf, Wasiu Akintunde; Yusuf, Sulaiman Adesina (Journal of Scientific Agriculture, 2017)
It is widely acknowledged that access to financial services plays a critical role in helping poor people strengthen their economic potentials, increase their asset base and diminish their vulnerabilities to external shocks. However, poor people have very limited access to financial services provided by the formal financial institutions due to the procedures outlined for accessing such loans. In recent time, Microcredit has received global attention owing to its claim in alleviating poverty. This study investigates the impact of microcredit program on poverty reduction among rural households in Saki East Local Government area of Oyo State using logit model and propensity score matching techniques to prove the impact. Findings revealed a negative, non-significant impact of microcredit on poverty reduction among rural households. Therefore, it is recommended that microcredit program should be implemented along with other poverty alleviation strategies.